A Hybrid Transdimensional Evolutionary Algorithm for Dynamical System Control Multicriteria Optimization - Vladimir A. Serov; Evgeny M. Voronov; Evgenia L. Dolgacheva; Elizaveta Y. Kosyuk (Engineering Proceedings, 2023)
The article develops a new hybrid evolutionary algorithm for the optimal control law multicriteria synthesis of a dynamical system based on transdimensional search models. The transdimensional search model implies the combined usage of finite-dimensional and infinite-dimensional multicriteria optimization evolutionary algorithms, implementing the stages of the global approximate and local clarifying search for optimal solutions. A comparative analysis of the effectiveness of various hybrid transdimensional models of the evolutionary search is carried out for the problem of the bioreactor program control optimal law multicriteria synthesis. It is shown that the transdimensional hybridization of evolutionary algorithms using infinite-dimensional search models provides a higher solving accuracy of the problem.